Water Governance Conflict in Kupang: between Limited Water Debit versus Commercialization - Dhosa, Didimus Dedi (Sodality: Jurnal Sosiologi Pedesaan, 2024)
This study aims to present the long-standing water governance dilemma in Kupang, East Nusa Tenggara, which has never been fully resolved. On the one hand, the people of Kupang City and Kupang Regency experience water shortages during the dry season. On the other hand, the practice of water commercialization appears to be carried out by local political economy elites in a vulgar and massive manner. Commercialization is understood as an effort involving a set of rules, policies, and norms that empower the market to provide clean water, and even produce and distribute water to citizens. This research was a qualitative study that employed in-depth interviews with 20 informants, observations at 5 water selling locations, and focus group discussions with drinking water customers. Using the commercialization perspective, this paper challenged the view that water scarcity in Kupang is due to limited water debit, rapid population growth, and low rainfall. This study found that the water problem in Kupang was caused by the massive commercialization of water, which was dominated by the private sector with government support through water sales operation permits, as well as illegal water drilling by local communities.